The first record of caeculid mites from the Cretaceous amber of Myanmar with notes on the phylogeny of the family - Porta, Andrés O.; Proud, Daniel N.; Franchi, Ezequiel; Porto, Willians; Epele, María Bernarda; Michalik, Peter (Zootaxa, 2019)
Procaeculus coineaui sp. nov. from Cretaceous Burmese amber is described and its phylogenetic position discussed. This fossil taxon is the first caeculid mite known from Burmese amber and constitutes the earliest record of the family. The genus Procaeculus is redefined to include the new fossil species and internal relationships between genera of the family are discussed based on a phylogenetic hypothesis.